PENERAPAN METODE PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS UNTUK ANALISA PERUBAHAN PENGGUNAAN LAHAN (Studi Kasus: Kawasan Danau Maninjau) (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2014)
Studies of changes in land use is very important, because changes in land use have an impact on the physical and social environment. The purpose of this study was to determine the use and change of spatial land in the area of Lake Maninjau by using satellite images and research in the field. The method used is the method of remote sensing image interpretation, survey method and descriptive analysis based spatial. Land use has changed between 1989 and 2014. The use of the forest land is the largest change is an area of 1989 ha 32.350.59, 27.580.50 20.175.93 ha ha in 2002 and 2014. The pattern of land use changes spatially in Region Maninjau follow the main activity of most of the population in agriculture. Most forest land is converted. Forest land converted to mixed farms are the most extensive in Nagari Tanjung Sani on the west side of the lake Maninjau (30 565 ha) and in Nagari Sungai Batang in the east of the lake Maninjau (31 831 ha).Keywords: changes in land use, satellite images, field checks, the Lake Maninjau